Use of Anthropometry Versus Ultrasound for the Assessment of Body Fat and Comorbidities in Children With Obesity. Issue 6 (December 2020) - El-Koofy, Nehal; Soliman, Hend; Elbarbary, Mennat-Allah; Garhy, Al Shimaa El; Sheba, Maha; Fouad, Hanan
ABSTRACT: Objectives: We aimed to examine the association between abdominal fat measured by ultrasound and anthropometric indices in children with obesity, and those with normal weight. We also examined the association between anthropometry and fat measures in the prediction of comorbidities in children with obesity. Methods: Forty children with body mass index of >95th percentile were included as cases, and a comparable group of 32 healthy average-weight peers were included as controls in this study. All children underwent clinical assessment, anthropometric measures, and evaluation of abdominal subcutaneous fat (SCF) and visceral fat by ultrasound. Fasting blood sugar, serum transaminases, and lipid profile of all the included children were also evaluated. Results: Children with obesity had a mean age of 8.7 ± 2.9 years (range 3–13). The SCF and intraperitoneal fat (IPF) values correlated well with each other and with anthropometric measurements in children with obesity. Among all the included cases, 90% were metabolically unhealthy, 70% had hypertension, 52.5% had dyslipidemia, and 22.5% had echogenic liver. Anthropometric measures, abdominal SCF and IPF were higher in children with complications. SCF was observed as a good predictor for hepatic echogenicity among the measured ultrasound parameters ( P : 0.03, odds ratio 4.6). The best cutoff value for SCF in cases with hepatic echogenicity was 23.2 mm with an overall accuracy of 80%. Conclusions: In children with obesity, abdominal SCF and IPF correlated well with anthropometric measures and were higher in children with comorbidities. This finding, however, did not predict comorbidities apart from those with echogenic liver. Abstract : Supplemental Digital Content is available in the text